Sickness benefit claims due to mental disorders in Brazil: associations in a population-based study Benefícios auxílio-doença devido a transtornos mentais no Brasil: associações em um estudo de base-populacional - Anadergh Barbosa-Branco; Ute Bültmann; Ivan Steenstra (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study aims to determine the prevalence and duration of sickness benefit claims due to mental disorders and their association with economic activity, sex, age, work-relatedness and income replacement using a population-based study of sickness benefit claims (> 15 days) due to mental disorders in Brazil carried out in 2008. The prevalence of mental disorders was 45.1 claims per 10,000 workers. Prevalence and duration of sickness benefit claims due to mental disorder were higher and longer in workers aged over 40 years. Prevalence of claims was 73% higher in women but duration of sickness benefit claims was longer in men. Prevalence rates for claims differed widely according to economic activity, with sewage, residential care and programming and broadcasting activities showing the highest rates. Claims were deemed to be work-related in 8.5% of cases with mental disorder showing low work-relatedness in Brazil. A wide variation of prevalence and duration between age, economic activity and work-relatedness was observed, suggesting that working conditions are a more important factor in mental disorder work disability than previously assumed. Este estudo visa determinar a prevalência e a duração dos benefícios auxílio-doença devidos à doença mental e sua associação com atividade econômica, sexo, idade, relação com o trabalho, e reposição salarial. Estudaram-se os benefícios auxílio-doença por doença mental concedidos no Brasil em 2008. Analisou-se a associação entre benefícios auxílio-doença e sexo, idade, atividade econômica, relação com o trabalho e reposição salarial. Doença mental representou 10.7% do total de benefícios auxílio-doença em 2008, com prevalência de 45,1/10 mil trabalhadores. A prevalência e a duração dos benefícios auxílio-doença foram maiores e mais longos entre trabalhadores ≥ 40 anos de idade; mulheres tiveram prevalência 73% maior do que homens, mas com menor duração. As prevalências variaram amplamente entre atividade econômica, sendo esgoto, saúde da família e rádio e televisão aquelas com as maiores taxas. A relação com o trabalho foi caracterizada em 8,5% dos benefícios. Doença mental mostrou baixa relação com o trabalho, mas com ampla variação na prevalência e na duração dos benefícios auxílio-doença em relação à idade, sexo e atividade econômica, sugerindo que as condições de trabalho constituem fator mais importante para incapacidade do que o presumido.